Continuous surveillance of potentially zoonotic avian pathogens detects contemporaneous occurrence of highly pathogenic avian influenza viruses (HPAIV H5) and flaviviruses (USUV, WNV) in several wild and captive birds - Anne Günther; Anne Pohlmann; Anja Globig; Ute Ziegler; Sten Calvelage; Markus Keller; Dominik Fischer; Christoph Staubach; Martin H. Groschup; Timm Harder; Martin Beer (Emerging Microbes and Infections)
Three avian viral pathogens circulate in Germany with particular importance for animal disease surveillance due to their zoonotic potential, their impact on wild bird populations and/or poultry farms: Highly pathogenic (HP) avian influenza virus (AIV) of subtype H5 (HPAIV H5), Usutu virus (USUV), and West Nile virus (WNV). Whereas HPAIV H5 has been mainly related to epizootic outbreaks in winter, the arthropod-borne viruses USUV and WNV have been detected more frequently during summer months corresponding to peak mosquito activity. Since 2021, tendencies of a potentially year-round, i.e. enzootic, status of HPAIV in Germany have raised concerns that Orthomyxoviruses (AIV) and Flaviviruses (USUV, WNV) may not only circulate in the same region, but also at the same time and in the same avian host range. In search of a host species group suitable for a combined surveillance approach for all mentioned pathogens, we retrospectively screened and summarized case reports, mainly provided by the respective German National Reference Laboratories (NRLs) from 2006 to 2021. Our dataset revealed an overlap of reported infections among nine avian genera. We identified raptors as a particularly affected host group, as the genera Accipiter, Bubo, Buteo, Falco, and Strix represented five of the nine genera, and highlighted their role in passive surveillance. This study may provide a basis for broader, pan-European studies that could deepen our understanding of reservoir and vector species, as HPAIV, USUV, and WNV are expected to further become established and/or spread in Europe in the future and thus improved surveillance measures are of high importance.